Dielectric Spectroscopy can Predict the Effect of External AC Fields on the Dynamic Adsorption of Lysozyme - Benavidez, Tomás Enrique (2022)
This report describes the application of dielectric spectroscopy as a simple and fast way to guide protein adsorption experiments. Specifically, the polarization behavior of a layer of adsorbed lysozyme was investigated using a triangular-wave signal with frequencies varying from 0.5 to 2 Hz. The basic experiment, which can be performed in less than 5 min and with a single sample, not only allowed confirming the susceptibility of the selected protein towards the electric signal but also identified that this protein would respond more efficiently to signals with lower frequencies. To verify the validity of these observations, the adsorption behavior of lysozyme onto optically transparent carbon electrodes was also investigated under the influence of an applied alternating potential. In these experiments, the applied signal was defined by a sinusoidal wave with an amplitude of 100 mV and superimposed to +800 mV (applied as a working potential) and varying the frequency in the 0.1–10000 Hz range. The experimental data showed that the greatest adsorbed amounts of lysozyme were obtained at the lowest tested frequencies (0.1–1.0 Hz), results that are in line with the corresponding dielectric features of the protein.